A study on the imposition of legal obligations upon states to intervene: operationalizing the Responsibility to Protect (R2P) / Afiqah Abdul Razak, Mohd Faizal Hiqram Azmi and Noor Hannah Mohd Nasir - Mohd Nasir, Noor Hannah; Abdul Razak, Afiqah; Azmi, Mohd Faizal Hiqram (Faculty of Law, 2013)
This project paper discusses the status of the doctrine of Responsibility to Protect (R2P) in relation to international law and seeks to establish whether R2P creates legal obligations unto the international community to take the appropriate measures in situations of mass atrocities. The project paper begins with an outline of our research proposal which works to draw the focus of our research to an introduction and general background of R2P. Our project paper further comprises of the conception of R2P alongside the obstacles faced in imposing this doctrine as an international duty. Furthermore, this project paper explores two possibilities in which R2P may impose legal obligations unto States: whether, firstly, R2P introduces a new rule of customary international law or whether, secondly, R2P establishes obligations by extending upon existing rules of jus cogens. Apart from that, this project paper analyzes the two recent cases of Libya and Cote d’Iviore wherein measures echoing the doctrine of R2P were invoked by the international community via the United Nations Security Council. Based on our findings on all these matters, this project paper shall, lastly, narrow down our research to several recommendations as to the imposition of R2P as an obligation under international law.